Inclusive jet production in pp(macro) collisions. - Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Alves, G; Amos, N; Anderson, E; Baarmand, M; Babintsev, V; et al. (American Inst of Physics, 2001)
We report a new measurement of the pseudorapidity (eta) and transverse-energy ( E(T)) dependence of the inclusive jet production cross section in pp(macro) collisions at square root of s = 1.8 TeV using 95 pb(-1) of data collected with the D0 detector at the Fermilab Tevatron. The differential cross section d(2)sigma/(dE(T)d eta) is presented up to eta = 3, significantly extending previous measurements. The results are in good overall agreement with next-to-leading order predictions from QCD and indicate a preference for certain parton distribution functions.